The Routledge handbook of tourism experience management and marketing - Dixit, Saurabh Kumar, 1979- (Routledge international handbooks, 2020)
"The Routledge Handbook of Tourism Experience Management and Marketing offers a comprehensive and thorough inquiry into both customary and emergent issues of tourism experience and co - creation. Drawing together contributions from 83 authors from 28 countries with varied backgrounds and interdisciplinary interests, the handbook highlights multiple representations and interpretations of the theme. It also integrates a selection of illustrative global case studies to effectively present its chapter contents. Tourism experience drives the contemporary tourist's behavior as they travel in pursuit of experiencing unique and unusual destinations and activities. Creating a memorable and enduring experience is therefore a prerequisite for the all tourism business organizations irrespective of the nature of their products or services. This handbook focuses on conceptualizing, designing, staging, managing and marketing paradigms of tourism experiences from both supply and demand perspectives. It sheds substantial light on the contemporary theories, practices and future developments in the arena of experiential tourism management and marketing. Encompassing the latest thinking and research themes, this will be an essential reference for upper-level students, researchers, academics and industry practitioners of hospitality as well as those of tourism, gastronomy, management, marketing, consumer behavior, cultural studies, development studies and international business, encouraging dialogue across disciplinary boundaries"--